Penggunaan Gawai dalam Mendukung Efektivitas Pembelajaran Bahasa di Era Society 5.0 - Bagus Wahyu Setyawan; Memet Sudaryanto (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2022)
The development of technology in the digital era is increasingly prevalent and sophisticated. One of them is the development of gadgets which is characterized by the increasing number of features and applications offered from each gadget development company. This research focuses on describing and explaining the use of gadgets in schools to support and support academic activities in the school environment. Research is in the form of qualitative descriptive research using a case study approach. The source of data in this school is the academic activities contained in the school environment. The research data was obtained by conducting observations and interviews with several speakers. The collected research data is then analyzed using interweaving analysis techniques and interactive analysis, with the following stages of the data reduction process, the data presentation process, and finally the conclusion drawing process. To test the validity of the data used data triangulation techniques. The results of the research obtained, at the research site, it turned out that the role of gadgets was used to support and support the learning process. The gadgets used include laptops, cellphones, and computers. The three varieties of gadgets are used by students and teachers as a means of facilitating communication, disseminating information, means of obtaining and finding references, making learning administration and learning media, as well as other supporting activities such as counting fungi, making applications, and programming. So, it can be said that gadgets have a supporting and supporting function in academic activities at school.